Ricardo Palma, ¿dueño de un semanario? - Varillas Montenegro, Alberto (2019)
Ricardo Palma made his firsts attemps as a journalist while still attending high school. However, only few papers have been devoted to his work as such and none of them has been able to study his weekly newspaper El Burro, given the fact that the only existing copy was seriously damaged in the 1943 fire that destroyed the Peruvian National Library, especially its newspaper archives. This work deals with El Burro and emphasizes the importance that this type of publications held within the Peruvian 19th century life.